2006
DOI: 10.1124/jpet.106.106484
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Combined Chemical Modifications to Enhance the Blood-Brain Barrier Permeability and Pharmacological Activity of Endomorphin-1

Abstract: The endogenous -opioid receptor agonist, endomorphin (EM)-1, cannot be delivered into the central nervous system (CNS) in sufficient quantity to elicit analgesia when given systemically because it is severely restricted by the blood-brain barrier (BBB). To improve the physicochemical characteristics of EM-1 and subsequently achieve greater BBB permeation, we synthesized a series of EM-1 analogs by combining successful chemical modifications, including N-terminal cationization, Cterminal chloro-halogenation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 28 publications
6
47
0
2
Order By: Relevance
“…The lipophilicity (Liu et al 2006a) is expressed as log P, log D or delta log P. The partition coefficient (P) (Ecker and Noe 2004;Kumar et al 2007;Liu et al 2006a) for test compounds is defined as the concentration ratio of test compound found in the organic phase such as octanol (C org [nl -3 ]) and that in the aqueous phase (C wat [nl -3 ]), quantified as log P: BW body weight, GFR glomerular filtration rate (Lin 1998) log P ¼ log…”
Section: Lipophilicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The lipophilicity (Liu et al 2006a) is expressed as log P, log D or delta log P. The partition coefficient (P) (Ecker and Noe 2004;Kumar et al 2007;Liu et al 2006a) for test compounds is defined as the concentration ratio of test compound found in the organic phase such as octanol (C org [nl -3 ]) and that in the aqueous phase (C wat [nl -3 ]), quantified as log P: BW body weight, GFR glomerular filtration rate (Lin 1998) log P ¼ log…”
Section: Lipophilicitymentioning
confidence: 99%
“…After administering the test compound intravenously or intracerebroventricularly into the animal, the tail flick withdrawal is evaluated by immersing the animal's tail in hot water (55°C). The latency to withdrawal is measured at different time points in order to construct the time curve (Kleczkowska et al 2010;Liu et al 2006a). The dose producing 50% of the maximum response (i.e.…”
Section: Antinociception Testmentioning
confidence: 99%
“…132 Inspired by the ancient Chinese ''Yin'' and ''Yang'' balance theory, a series of EM-1 analogues 140-149 were synthesized to enhance stability and penetration to the CNS. We combined the useful methods of structural modification like cationization of the amino acid N-terminus, halogenation of the amino acid C-terminus, which can achieve a balance between ''anions'' and ''cations,'' and D-Ala, Sar, D-Pro-Gly substitution in the second position.…”
Section: A Cationizationmentioning
confidence: 99%
“…Metabolic stability study was carried out according to previously reported method with some modifications (Liu et al 2006). Male Wistar rats (ca.…”
Section: Metabolic Stability Studymentioning
confidence: 99%